2012
DOI: 10.1128/cvi.05433-11
|View full text |Cite
|
Sign up to set email alerts
|

A New MIC1-MAG1 Recombinant Chimeric Antigen Can Be Used Instead of the Toxoplasma gondii Lysate Antigen in Serodiagnosis of Human Toxoplasmosis

Abstract: This study presents an evaluation of the MIC1 (microneme protein 1)-MAG1 (matrix antigen 1) Toxoplasma gondii recombinant chimeric antigen for the serodiagnosis of human toxoplasmosis for the first time. The recombinant MIC1-MAG1 antigen was obtained as a fusion protein containing His tags at the N-and C-terminal ends using an Escherichia coli expression system. After purification by metal affinity chromatography, the chimeric protein was tested for usefulness in an enzyme-linked immunosorbent assay (ELISA) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Their research demonstrated that the IgM Rec-ELISA found 70% of serum samples from infants with congenital toxoplasmosis to be positive, whereas the commercially available assays used (ELFA-IgM [bioMérieux, France] or ETI-TOXOK-M [DiaSorin, Italy]) found positive results for only 35% of the infected infants (46). Furthermore, different chimeric proteins have also been shown to be very effective in detecting specific anti-T. gondii antibodies in human serum samples (Table 3) (75)(76)(77)(78)(79). In 2012, Holec-Gąsior et al (76) showed that the sensitivity of the IgG ELISA for the MIC1-MAG1 chimeric protein was almost as high as that for the Toxoplasma lysate antigen (TLA), 90.9% and 91.8%, respectively, whereas the sensitivities of IgG ELISAs for the mixture of two recombinant proteins (rMAG1 and rMIC1ex2) or for single recombinant antigens were definitely lower, 69.1% for the mixture, 75.5% for rMIC1ex2, and 60% for rMAG1.…”
Section: Chimeric Antigens and Multiepitope Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research demonstrated that the IgM Rec-ELISA found 70% of serum samples from infants with congenital toxoplasmosis to be positive, whereas the commercially available assays used (ELFA-IgM [bioMérieux, France] or ETI-TOXOK-M [DiaSorin, Italy]) found positive results for only 35% of the infected infants (46). Furthermore, different chimeric proteins have also been shown to be very effective in detecting specific anti-T. gondii antibodies in human serum samples (Table 3) (75)(76)(77)(78)(79). In 2012, Holec-Gąsior et al (76) showed that the sensitivity of the IgG ELISA for the MIC1-MAG1 chimeric protein was almost as high as that for the Toxoplasma lysate antigen (TLA), 90.9% and 91.8%, respectively, whereas the sensitivities of IgG ELISAs for the mixture of two recombinant proteins (rMAG1 and rMIC1ex2) or for single recombinant antigens were definitely lower, 69.1% for the mixture, 75.5% for rMIC1ex2, and 60% for rMAG1.…”
Section: Chimeric Antigens and Multiepitope Peptidesmentioning
confidence: 99%
“…Furthermore, different chimeric proteins have also been shown to be very effective in detecting specific anti-T. gondii antibodies in human serum samples (Table 3) (75)(76)(77)(78)(79). In 2012, Holec-Gąsior et al (76) showed that the sensitivity of the IgG ELISA for the MIC1-MAG1 chimeric protein was almost as high as that for the Toxoplasma lysate antigen (TLA), 90.9% and 91.8%, respectively, whereas the sensitivities of IgG ELISAs for the mixture of two recombinant proteins (rMAG1 and rMIC1ex2) or for single recombinant antigens were definitely lower, 69.1% for the mixture, 75.5% for rMIC1ex2, and 60% for rMAG1. Thus, the MIC1-MAG1 recombinant chimeric antigen has the potential to replace the TLA in the IgG ELISA.…”
Section: Chimeric Antigens and Multiepitope Peptidesmentioning
confidence: 99%
“…Upgrading these tests with recombinant proteins will improve their sensitivity and specificity which will have major advantages for the diagnosis of toxoplasmosis and this will reduce the problems of antigen standardization and assay reproducibility which is a major problem of diagnostic laboratories worldwide [6]. The surface antigens SAG1 (p30) [7][8][9][10][11], SAG2 (P22) [7,9,10]; the dense granule antigens GRA1 (P24) [12][13][14][15], GRA2 (P28) [16,17], GRA6 (P32) [14,18,19] and GRA7 (P29) [9,10,15,20,21] the rhoptry antigens ROP1 (P66) [17,22,23]; the microneme antigens MAG1 [24,25] and MIC1 [24,26] bodies in humans and animals. Toxoplasma gondii Subtilisin-like protein 1 (TgSUB1) have been suggested to play an important role in survival of parasite.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of IgG antibody titers against MAG1 were found in T. gondii-infected humans and pigs (Gamble et al, 2000;Di Cristina et al, 2004). Among the several recombinant proteins of T. gondii, MAG1 has been demonstrated to be a good candidate for the serodiagnosis of toxoplasmosis (Holec et al, 2007;Holec-Gasior et al, 2012). In this study, the recombinant MAG1 (rMAG1) protein was evaluated as a potential diagnostic marker of T. gondii infection in dogs by an indirect ELISA method.…”
mentioning
confidence: 99%